COVID‐19 and Resilience in Schools: Implications for Practice and Policy. Issue 3 (20th December 2021) - Luthar, Suniya S.; Pao, Lisa S.; Kumar, Nina L.
Abstract: This is a mixed‐methods study of risk and resilience in a sample of over 14, 000 students from 49 schools, assessed during the first 3 months of COVID‐19 in the United States. Over a third of students were of color and almost a third received financial aid. Participation rates were typically 90–99%. Overall, rates of clinically significant depression and anxiety were lower during distance learning in 2020 as compared to parallel rates documented during 2019, with a few exceptions. Hispanic students did not show reductions in depression rates, nor did gender non‐binary youth. Analyses of multiple risk and protective factors showed that in relation to depression, the most potent predictor was parent support, with effect sizes at least twice as high as those for any other predictor. Other robust predictors of depression included efficacy of learning online and concerns heard by school adults . In predicting to anxiety, parent support again had the largest effect sizes, followed by concerns heard at school, students' worries about their futures, and worries about grades . In general, the absence of protective factors was more likely to be linked with high distress among youth of color than White students, and among girls and gender non‐binary students as compared to boys. At a policy level, the findings call for concerted attention to the well‐being of adults charged with caring for youth. Parents' mental health has been increasingly threatened with the protracted stress linked with the pandemic. Thus, all avenues must be considered toward providing them with support—using feasible, community‐based interventions—as this is always the most important step in fostering children's resilience through adversity. Additionally, schools' expectations about learning will have to be adjusted. As educators try to make up for academic losses during the pandemic, they must avoid high workloads detrimental for students' mental health (and thus ability to learn). Finally, there must be ongoing institutional mental health support for teachers, counselors, administrators, and staff. Many of these adults have provided critical safety nets for youth since the start of the pandemic and are themselves at high risk for burnout. In conclusion, findings clearly show that if a central societal goal is to maximize resilience among youth through the continuing pandemic‐related challenges, we will have to deliberately prioritize an "upstream" approach, ensuring ongoing support for the adults who take care of them in their everyday lives. There must be ongoing institutional mental health support for teachers, counselors, administrators, and staff. Many of these adults have provided critical safety nets for youth since the start of the pandemic and are themselves at high risk for burnout.